The Expression of Epstein-Barr virus in Breast cancer in relation to age - Hanna, Ban Jamal; Habib, Manal Adnan; Al-Mosawi, Huda Adnan (AL-Kindy College Medical Journal, 2011)
Background: Breast cancer is the most commonmalignancy affecting females worldwide. The associationof Epstein-Barr virus (EBV) with this cancer is a longstandinginterest to this field.Aim: to investigate the presence of EBV in breast tumortissue in relation to age.Patients and Methods: Paraffin-embedded tissue blocksfrom 45 female patients with breast tumors (ranged in agefrom 28 to 85 years) were retrieved. The cases weregrouped into two categories: group (A): included 30 caseswith breast carcinoma and group (B): included 15 caseswith benign breast diseases as a control group .Theexpression of EBV protein was examinedimmunohistochemically.Results: Twelve (40%) of the 30 breast cancer cases(group A) were reported as positive for EBV expressionand significantly higher in patients less than 40 years age(P= 0.026).Conclusion: the results of the current study might refer tothe significance of EBV expression in breast tissue ofyoung patients with breast cancer.